Measurement of ZZ production in leptonic final states at sqrt[s] of 1.96 TeV at CDF. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
In this Letter, we present a precise measurement of the total ZZ production cross section in pp collisions at sqrt[s]=1.96  TeV, using data collected with the CDF II detector corresponding to an integrated luminosity of approximately 6  fb(-1). The result is obtained by combining separate measurements in the four-charged (ℓℓℓ' ℓ') and two-charged-lepton and two-neutral-lepton (ℓℓνν) decay modes of the Z boson pair. The combined measured cross section for pp → ZZ is 1.64(-0.38)(+0.44)  pb. This is the most precise measurement of the ZZ production cross section in 1.96 TeV pp collisions to date.